2017
DOI: 10.2196/preprints.9374.a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diabetes-Specific Formulae Versus Standard Formulae as Enteral Nutrition to Treat Hyperglycemia in Critically Ill Patients: Protocol for a Randomized Controlled Feasibility Trial

Abstract: Background: During critical illness, hyperglycemia is prevalent and is associated with adverse outcomes. While treating hyperglycemia with insulin reduces morbidity and mortality, it increases glycemic variability and hypoglycemia risk, both of which have been associated with an increase in mortality. Therefore, other interventions which improve glycemic control, without these complications should be explored. Nutrition forms part of standard care, but the carbohydrate load of these formulations has the potent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Diverse studies have shown the important role of DSF for type-2 diabetic patients management in fields such as glycemic control (both capillary and plasma glucose), lowering insulin requirements, effective weight loss as well as reducing the risk of acquired infections in hospitalized patients [32]. Compared to standard formulas, DSF have lower glycemic index and its components are targeting a population who needs normoprotein-caloric diet [34]. An ideal nutritional formula for all types of diabetic patients has not yet been developed.…”
Section: Sci Forschenmentioning
confidence: 99%
“…Diverse studies have shown the important role of DSF for type-2 diabetic patients management in fields such as glycemic control (both capillary and plasma glucose), lowering insulin requirements, effective weight loss as well as reducing the risk of acquired infections in hospitalized patients [32]. Compared to standard formulas, DSF have lower glycemic index and its components are targeting a population who needs normoprotein-caloric diet [34]. An ideal nutritional formula for all types of diabetic patients has not yet been developed.…”
Section: Sci Forschenmentioning
confidence: 99%